Application of Nanomaterials in Stem Cell‐Based Therapeutics for Cardiac Repair and Regeneration. Issue 11 (15th January 2023) - Qiu, Jie; Liu, Xiang‐Ju; You, Bei‐An; Ren, Na; Liu, Hong
Abstract: Cardiovascular disease is a leading cause of disability and death worldwide. Although the survival rate of patients with heart diseases can be improved with contemporary pharmacological treatments and surgical procedures, none of these therapies provide a significant improvement in cardiac repair and regeneration. Stem cell‐based therapies are a promising approach for functional recovery of damaged myocardium. However, the available stem cells are difficult to differentiate into cardiomyocytes, which result in the extremely low transplantation efficiency. Nanomaterials are widely used to regulate the myocardial differentiation of stem cells, and play a very important role in cardiac tissue engineering. This study discusses the current status and limitations of stem cells and cell‐derived exosomes/micro RNAs based cardiac therapy, describes the cardiac repair mechanism of nanomaterials, summarizes the recent advances in nanomaterials used in cardiac repair and regeneration, and evaluates the advantages and disadvantages of the relevant nanomaterials. Besides discussing the potential clinical applications of nanomaterials in cardiac therapy, the perspectives and challenges of nanomaterials used in stem cell‐based cardiac repair and regeneration are also considered. Finally, new research directions in this field are proposed, and future research trends are highlighted. Abstract : Nanomaterials are widely used in cardiac repair and regeneration. In this review, the current status and limitations of stem cell‐based cardiac therapy as well as the recent advances in nanomaterials and their advantages and disadvantages are summarized. Moreover, challenges of nanomaterials used in stem cell‐based therapeutics are discussed, and new research directions in cardiac tissue engineering are proposed.